Preconception Care: The Perfect Opportunity for Health Care Providers to Advise Lifestyle Changes for Hypertensive Women - Bombard, Jennifer M. (Am J Health Promot, 2013)
PURPOSE: To provide estimates for prevalence of health care provider advice offered to reproductive-aged women and to assess their association with behavior change. DESIGN: Cross-sectional study using the 2009 Behavioral Risk Factor Surveillance System. SETTING: Nineteen states/areas. SUBJECTS: Women aged 18 to 44 years with a self-reported history of hypertension or current antihypertensive medication use (n = 2063). MEASURES: Self-reported hypertension; sociodemographic and health care access indicators; and provider advice and corresponding self-reported behavior change to improve diet, limit salt intake, exercise, and reduce alcohol use. ANALYSIS: We estimated prevalence and prevalence ratios for receipt of provider advice and action to change habits. We calculated 95% confidence interval (CI) and used χ(2) tests to assess associations. RESULTS: Overall, 9.8% of reproductive-aged women had self-reported hypertension; most reported receiving advice to change eating habits (72.9%), reduce salt intake (74.6%), and exercise (82.1%), and most reported making these changes. Only 44.7% reported receiving advice to reduce alcohol intake. Women who received provider advice were more likely to report corresponding behavior change compared to those who did not (prevalence ratios ranged from 1.3 [95% CI, 1.2–1.5, p < .05] for exercise to 1.6 [95% CI, 1.4–1.8, p < .05] for reducing alcohol use. CONCLUSION: Health care providers should routinely advise hypertensive reproductive-aged women about lifestyle changes to reduce blood pressure and improve pregnancy outcomes.